Pendidikan Antikorupsi: Penanaman Karakter Jujur melalui Kantin Kejujuran di Sekolah Dasar - Restuningtyas, Arrum Bunga; Utomo, Arief Cahyo (University of Muhammadiyah Malang, 2024)
The study aims to determine the honesty canteen's implementation, impact, and constraints. The type of research is qualitative descriptive with a case study method at SDN Polokarto 04. The type of data used is qualitative data. Data sources came from the principal, teachers, and students from Grade I to Grade VI. Data collection techniques used observation, interviews, and documentation. The study used three indicators of honesty: 1) not lying, 2) not taking items that do not belong to them, and 3) admitting mistakes. The results showed that implementing the honesty canteen uses the concept of self-service; buyers take their food and drinks to be purchased, pay themselves, and take their own change if needed. The most influential impact of implementing the honesty canteen in elementary schools is a behavior or character cultivation change. Embedded characteristics include practicing honesty with oneself and others and fostering independence and responsibility. Another impact seen from the indicators of honesty is that students are accustomed to speaking according to reality to create a transparent and trustworthy environment, students have responsibility regarding their belongings and do not take other people's property, and students dare to admit mistakes and can make it a lesson. The obstacles elementary school students face are difficulty counting and the absence of change when transacting in the honest canteen.